Efficient and eco-friendly synthesis of 2-amino-1,3-selenazoles in an ionic liquid/water system under ambient conditions - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Arkivoc, 2008)
An efficient and eco-friendly synthesis of 2-amino-1,3-selenazoles in ionic liquid/water solvent system is described. The paper describes synthesis of 2-amino-1,3-selenazoles by condensation of various phenacyl bromide with selenourea under ambient conditions in short reaction times. This protocol has notable advantages such as the absence of any added catalyst, simple operation and excellent yields of products and recyclability of the ionic liquid.
Keywords: 2-Amino-1; 3-selenazoles; ambient conditions; heterocycles; ionic liquid/water system; selenoureas; substituted phenacyl bromide